The Effect of Canva on Instagram Application Media on Students’ Ability to Writing Descriptive Text at Grade X Of Sma Negeri 1 Air Joman In 2025/2026 Academic Year - Khoirun Niswa Siregar; Sri Rahayu (Institute of Advanced Knowledge and Science, 2026)
This empirical study investigated the significant effect of integrating the Canva application with the Instagram social media platform on the capability of tenth-grade students at SMA Negeri 1 Air Joman to write descriptive texts in the academic year of 2025/2026. The primary constraint underlying this research was the students deficient productive writing skills due to conventional expository teaching methods, causing limited vocabulary acquisition, poor structural alignment, and structurally disorganized presentation of descriptive paragraphs. This research utilized a quantitative approach with a quasi-experimental non-equivalent control group design. The chosen samples comprised two cluster groups: the control class (24 students) subjected to conventional methods and the experimental class (25 students) exposed to combined. Canva and Instagram interventions. Data collection incorporated written descriptive writing tests (pre-test and post-test) assessed via a modified analytical scoring rubric from Brown, comprising elements of content, organization, grammar, vocabulary, and writing mechanics. The experimental class registered a substantial post-test average score of 79.6, outperforming the control class which gathered 72.9. Statistical hypothesis testing using the Independent Sample t-test framework yielded a significant outcome where the observed value reached 5.59, drastically higher than the critical benchmark fable value of 2.03 at a significance margin of a-0.05 and degrees of freedom (df) 47. Consequently, the Null Hypothesis (Ho) was rejected, and the Alternative Hypothesis (Ha) was accepted. The research concludes that the pedagogical alignment of Canva and Instagram establishes a significantly positive effect on modernizing language learning processes and enhancing secondary students' descriptive paragraph performance. Keywords: Canva, Instagram, Descriptive Text and Writing SkillKeywords: Net Exports, Interest Rates, Foreign Debt, Foreign Exchange Reserves.